Bridging Artificial Intelligence and Revelation: Semantic Analysis on Chapter Al-‘Alaq in the Qur’an through the Artificial Neural Networks Perspective: Menjembatani Kecerdasan Buatan dan Wahyu: Analisis Semantik Surat Al-Alaq dalam Perspektif Jaringan Syaraf Tiruan - Alhubilah, Fahmi; Al Farisi, Mohamad Zaka Al Farisi; Supriadi, Rinaldi Supriadi (Institut Agama Islam Negeri Kerinci, 2025)
This article aims to elaborate the relationship between the principles of Artificial Neural Networks (ANN) in Artificial Intelligence (AI) and the scientific values contained in Surah Al-Alaq verses 1-5. The main focus of the research is the question: to what extent can the principles of learning and cognition in JST be semantically analyzed through the Qur'anic perspective, and whether the ethical values contained in the first revelation can provide conceptual guidance for the development of responsible AI. The method used is semantic analysis using Toshihiko Izutzu's approach, which examines the lexical and relational meanings of key words in Surat Al-Alaq. The results showed conceptual similarities between JST learning processes - such as data input, classification, and layered processing - and the command “Iqra'”, the concept of “Qalam”, and the Qur'anic emphasis on reason and knowledge. These findings indicate that the working principles of JSTs have philosophical counterparts in Islamic sacred texts, which emphasize progressive learning, truth-seeking, and sincere intentions in acquiring knowledge. Consequently, this study offers an ethical-conceptual framework for the development of value-based AI, particularly in the realms of Islamic education and humanistic technology. These results contribute to the discourse on the integration of Islamic science and modern science in an applicable manner and open opportunities for the development of a more transcendental AI ethic.